Which Factors Favour Becoming a Technology-Based & Highly Innovative Firm? The Role of Knowledge, Technological and Managerial Capabilities, and Entrepreneurs Education Background - Tomás González-Cruz; Jose Antonio Clemente; Sergio Camisón-Haba (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Split, Croatia, 6-8 September 2018, 2018)
Which resources and capabilities ease the change to become a Technology-Based and Highly Innovative Firm –TB&InnF–, focused in the creation of value to market? We analyse this question using a novel data panel assembled for 326 Spanish industrial firms, along the period 1984-2012. Our findings show the probability of becoming a TB&InnF growths when firms are able to accumulate a high endowment of knowledge and technological capabilities, and a managerial team with: experience, strong power position and previous technical and managerial education. Results also indicate the CEOs educational profile in management is preferable to a pure technical profile, because this complements firms knowledge and technological capabilities and enables the transformation of a scientific or technological project into a successful entrepreneurial innovation, which creates new value to market.
Keywords: M10; 330; technology-based & highly innovative firm; knowledge-based capabilities; technological capabilities; managerial capabilities; entrepreneurial education